2014
DOI: 10.3390/f5051053
|View full text |Cite
|
Sign up to set email alerts
|

Using VEGNET In-Situ Monitoring LiDAR (IML) to Capture Dynamics of Plant Area Index, Structure and Phenology in Aspen Parkland Forests in Alberta, Canada

Abstract: Abstract:The use of ceptometers and digital hemispherical photographs to estimate Plant Area Index (PAI) often include biases and errors from instrument positioning, orientation and data analysis. As an alternative to these methods, we used an In-Situ Monitoring LiDAR system that provides indirect measures of PAI and Plant Area Volume Density (PAVD) at a fixed angle, based on optimized principles and algorithms for PAI retrieval. The instrument was installed for 22 nights continuously from September 26 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Previous studies confirmed that lidar data are affected by rain (through refraction or reflection of the laser beam by moisture on the external surface of the scan head prism), and by wind (through random displacement of tree branches and leaves; Culvenor et al, 2014;Portillo-Quintero et al, 2014). Single rain-affected scans can be removed if accurate weather data are available (Portillo-Quintero et al, 2014).…”
Section: Data Filtering and Analysismentioning
confidence: 93%
“…Previous studies confirmed that lidar data are affected by rain (through refraction or reflection of the laser beam by moisture on the external surface of the scan head prism), and by wind (through random displacement of tree branches and leaves; Culvenor et al, 2014;Portillo-Quintero et al, 2014). Single rain-affected scans can be removed if accurate weather data are available (Portillo-Quintero et al, 2014).…”
Section: Data Filtering and Analysismentioning
confidence: 93%
“…The VEGNET is a TLS that automatically scans a forest plot and produces a vertical foliage density profile. Given its automated mode of operation and semipermanent installation, the VEGNET instrument is described as an in situ monitoring lidar (IML) (Culvernor et al, 2014;Portillo-Quintero et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For fine-scale tree structure representation, static terrestrial LiDAR (also referred to as static terrestrial laser scanning, TLS) mostly capable of characterizing structure details, such as vegetation density profiles (Ashcroft et al, 2014), was attempted to quantify and monitor ecosystem structural dynamics (Eitel et al, 2013). Portillo-Quintero et al (2014) utilized a TLS system to in-situ measure the dynamics of phenology. Calders et al (2015) operated spring phenology monitoring by manipulating high temporal resolution TLS measurements.…”
Section: Introductionmentioning
confidence: 99%